STANDAR INTERNASIONAL PENGELOLAAN KOLEKSIILMIAH IKAN - Tjakrawidjaja, Agus Hadiat (Research Center for Biology-Indonesian Institute of Sciences, 2001)
Indonesia, in Rio de Janeiros United Nations meeting (1992) was considered as one of the world mega biodiversity regions.The biodiversity richness also shown in the high variation of her fish species both fresh water and marine.Collection of scientific materials in a zoological museum is an imvaluable treasure of a country, and important in the study and conservation of biodiversity. This paper discusses aspects of international standard on fish scientific collection management including steps started from initial collection, processing, delivery, maintenance and material exchange for scientific purpose.